The Dynamic Effect of Disability on Work and Subjective Wellbeing in Australia - Melanie Jones; Kostas G. Mavromaras; Peter J. Sloane; Zhang Wei (Institute for the Study of Labor (IZA), 2015)
Using longitudinal data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey (2001-2013) we examine the relationship between the dynamics of work-limiting disability and employment, hours of work, earnings and life satisfaction. We employ two alternative classifications of the dynamic trajectories of disability and, in doing so, are able to explicitly consider the influence of disability exit in addition to examining onset by chronicity and severity. After controlling for unobserved individual heterogeneity, we find that the positive impact of disability exit is smaller in magnitude and shorter-lived than the negative impact of onset. Further, while individuals are found to recover from a one period disability within three years, there is no sign of adaptation even after ten years for those whose disability is chronic, defined as evident for three or more years post-onset, and severe.
Keywords: I10; J2; J31; J71; 330; disability; employment; hours of work; earnings; life satisfaction; HILDA